Reclaiming our hopes - Abd Razak, Dzulkifli (2010)
LAST Saturday was a memorable one for Universiti Sains Malaysia (USM). As early as 8am on a Ramadan morning, hundreds of students and staff gathered around the iconic Tasik Harapan to collectively perform a simple gesture that would bring back the lake to life — not that the Tasik is lifeless, but it is not the way it was before.